Enhancing Disaster Resilience through Risk Assessment and Sustainable Planning in the Lekki-Epe Corridor, Lagos - Badru, Gbolahan; Otusanya, Olayinka; Odunuga, Shakirudeen; Sadiku, Olalekan (Journal of Sustainable Natural Resources, 2026)
The resilience of coastal areas is seriously threatened by environmental degradation, urbanisation, and climate change. The study examines the vulnerability of the Lekki-Epe corridor in Lagos State, Nigeria, to flooding, with an emphasis on ecological risk and socio-economic impact, among other factors. Using geospatial analysis, Ordinary Weighted Average (OWA) and Multi-criteria Decision Analysis (MCDA), integrated vulnerability mapping was conducted to assess susceptibility levels across different areas. The results indicate that a substantial portion (69.3%) of the study area falls within the very vulnerable category, particularly in rapidly urbanising zones where wetland encroachment and poor drainage infrastructure exacerbate environmental hazards. The study emphasises how these vulnerabilities have social and economic repercussions, such as greater susceptibility to climate-induced floods, community displacement, infrastructure destruction, and economic disruptions. To enhance resilience, the results highlight the necessity of better land-use regulations, coordinated urban planning, and the utilisation of nature-based solutions. Additionally, there is a need for stronger environmental governance, building of flood-resistant infrastructure, and the use of geospatial technology for early warning and real-time monitoring of catastrophes. Future research should explore dynamic climate modelling, real-time vulnerability assessments, and participatory planning approaches to improve disaster risk reduction strategies. This study contributes to the growing discourse on urban disaster resilience, providing insights for policymakers, urban planners, and environmental scientists seeking to mitigate vulnerabilities in rapidly developing coastal regions.